GENERATION OF LONG DELAYS BETWEEN DYE-LASER PULSES BY OPTICAL-PUMPING VIA OPTICAL FIBERS - Ewart, P (1981)
A simple means of generating long optical delays is demonstrated. Pairs of laser excitation and probe pulses have been generated in such a way that the interaction geometry of the two beams remains fixed whilst the delay of the probe is varied.